An anthropological analysis of a cemetery at Inowrocław dated at Roman Era - Mucha, Elżbieta (Anthropological Review, 1978)
55 excavated during salvage project graves dated at Roman Era contained burned remains of human individuals (64.8%), unburned complete skeletons (16.7%) and parts of unburned skeletons (18.5%). On this material comprising sex and age estimates of all 55 individuals a paleodemographic analysis was performed (see tables 3 and 4). Unburned bones were subject to description by means of standard osteometric technique (tables 1 and 2).